1957
DOI: 10.1001/archinte.1957.00260020058010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mumps Orchitis with Adrenal Hormones

Abstract: Epididymo-orchitis occurs as a complication in the course of mumps in 18% to 43% of postpubertal males.1-4 Not only is gonadal involvement accompanied by severe local pain and systemic discomfort, but testicular atrophy is a sequel in about one-half of the cases, and sterility can result, although this is probably unusual.5,6 Of the various prophylactic measures that have been tried in males with epidemic parotitis, the administration of diethylstilbestrol has given encouraging results,7,8 and early injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1958
1958
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Abnormality of liver-function tests was mentioned by Petersdorf and Bennett (1957), and some possible disturbance was found in 6 of our 11 patients in whom it was sought. These patients were selected only in so far as they were among the last 13 patients in our series.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Abnormality of liver-function tests was mentioned by Petersdorf and Bennett (1957), and some possible disturbance was found in 6 of our 11 patients in whom it was sought. These patients were selected only in so far as they were among the last 13 patients in our series.…”
Section: Discussionmentioning
confidence: 82%
“…The latter appeared related to some extent to the duration of the swelling in that no cases where that had lasted for less than three days from admission (or five days from onset) showed complete atrophy seven months later. Petersdorf and Bennett (1957) observed 23 sporadic cases over a four-year period in three different hospitals treated with three different corticosteroids in varying doses for varying lengths of time without any controls, and concluded that the hormones exerted a beneficial effect when compared with the previously described natural history of the illness. Their impression that patients who responded by crisis were less likely to show atrophic changes during the few months after acute disease and that the prompt administration of 300 mg. of cortisone or its equivalent was most important in achieving this result is not borne out by our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation